Management and Service Quality Affecting the Survival of Small Retail Businesses in Northeastern Thailand - คูประทุมศิริ สถาพร; จิตติพันธ์ พิศมัย; ณัฐภัสสร ธนาบวรพาณิชย์ ณัฐภัสสร ธนาบวรพาณิชย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) examine the current conditions, problems, and obstacles related to service management; 2) investigate quality management and business operational capabilities for business survival; and 3) explore external environmental factors affecting management for the survival of small retail businesses in the northeastern region of Thailand. This study employed a qualitative research approach by utilizing secondary data and collecting opinions from 19 experts. The number of experts, who served as key informants, was determined based on the minimum sample size principle of the Delphi technique. A purposive sampling method was applied, including entrepreneurs with at least five years of experience and consistent business growth, as well as academics from relevant organizations. The findings revealed that: 1) small retail businesses in the Northeastern region operate under an adaptive management approach in response to fluctuating conditions and limited purchasing power. As a result, they face challenges related to economic constraints, resource limitations, and entrepreneurial capabilities, as well as a lack of systematic service management; 2) service quality management across five dimensions-tangibles, reliability, responsiveness, assurance, and empathy-together with business operational capabilities, including cost control, differentiation, and niche market focus, are key factors influencing business survival. In particular, maintaining strong customer relationships serves as a significant competitive advantage; and 3) External environmental factors-political, economic, social, technological, environmental, and legal-significantly influence business operations, acting as both pressures and supporting factors that require continuous adaptation by entrepreneurs to ensure long-term survival.